1993
DOI: 10.1111/j.1365-2672.1993.tb02788.x
|View full text |Cite
|
Sign up to set email alerts
|

Kidney bean lectin‐induced Escherichia coli overgrowth in the small intestine is blocked by GNA, a mannose‐specific lectin

Abstract: The reversible and dose-dependent hyperplastic growth of the small intestine and accelerated epithelial cell turnover caused by feeding rats with diets containing kidney bean lectin (PHA) increased the proportion of immature cells on the villi whose membrane and/or cytoplasm contained mainly simple, polymannosylated glycans. These new alpha-linked mannosyl terminals, particularly of the damaged epithelium, facilitated the preferential adherence of opportunistic Escherichia coli with mannose-sensitive Type 1 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 25 publications
2
59
1
1
Order By: Relevance
“…Raw red kidney beans as e species ATIN NAME COMMON NAME COMMENTS LECTIN REFERENCE r rats caused indigenous bacterial proliferation/overgrowth (e.g. aerobes, anaerobes and E. coli) in the jejunum and ileum (Wilson et al, 1980;Banwell et al, 1983 andPusztai et al 1993b). Bacterial proliferation was observed within 24 hours of PHA feeding, but counts fell progressively within 24-48 hours following reversion to a PHA-free diet (Banwell et al, 1988).…”
Section: Biological Effects In Fish General Considerationsmentioning
confidence: 99%
“…Raw red kidney beans as e species ATIN NAME COMMON NAME COMMENTS LECTIN REFERENCE r rats caused indigenous bacterial proliferation/overgrowth (e.g. aerobes, anaerobes and E. coli) in the jejunum and ileum (Wilson et al, 1980;Banwell et al, 1983 andPusztai et al 1993b). Bacterial proliferation was observed within 24 hours of PHA feeding, but counts fell progressively within 24-48 hours following reversion to a PHA-free diet (Banwell et al, 1988).…”
Section: Biological Effects In Fish General Considerationsmentioning
confidence: 99%
“…The role of lectins in bacterial enteric conditions was first demonstrated by Banwell et al (1988), whose results were later confirmed and extended by Pusztai et al (1993), Bardocz et al (1995) and Pusztai et al (1997). In their view, intestinal bacterial counts are higher in lectin-fed animals, but lectins also may exert beneficial influence by enhancing epithelial layer replacement.…”
Section: Soybean Lectinsmentioning
confidence: 52%
“…For example, soluble non-toxic lectins may be administered where their carbohydrate specificities are selected to compete for the glycosyl binding sites of the fimbrial adhesin. This approach is exemplified by the use of GNA, the snowdrop lectin, which is highly specific for 1,3a linked D-mannose units, to block the proliferation of type-1 fimbriated E. coli (Pusztai et al, 1993). Equally, the in vitro attachment of bacteria to cell surfaces can be effectively inhibited by oligosaccharides of appropriate structure (Sharon et al, 1981;Oyofo et al, 1988).…”
Section: Competitive Exclusionmentioning
confidence: 99%